2021
DOI: 10.3390/jcm10204783
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Practice of Early Prone Positioning in Invasively Ventilated COVID-19 Patients—Insights from the PRoVENT-COVID Observational Study

Abstract: We describe the incidence and practice of prone positioning and determined the association of use of prone positioning with outcomes in invasively ventilated patients with acute respiratory distress syndrome (ARDS) due to coronavirus disease 2019 (COVID-19) in a national, multicenter observational study, performed at 22 intensive care units in the Netherlands. Patients were categorized into 4 groups, based on indication for and actual use of prone positioning. The primary outcome was 28-day mortality. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 30 publications
(61 reference statements)
1
48
1
Order By: Relevance
“…Several observational studies reported high frequency use of prone ventilation in intubated COVID-19 patients with ARDS, which ranged from 60% to 79%. 28 , 29 , 30 , 31 This phenomenon may be explained by a greater predominance of moderate-to-severe hypoxemia among patients with COVID-19 pneumonia, resulting in a drastic rise in the occupancy of intensive care units. [32] Moreover, the adaptation of prone ventilation in COVID-19-related ARDS may have derived from the intervention that had been proven to be beneficial in ARDS of other causes in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies reported high frequency use of prone ventilation in intubated COVID-19 patients with ARDS, which ranged from 60% to 79%. 28 , 29 , 30 , 31 This phenomenon may be explained by a greater predominance of moderate-to-severe hypoxemia among patients with COVID-19 pneumonia, resulting in a drastic rise in the occupancy of intensive care units. [32] Moreover, the adaptation of prone ventilation in COVID-19-related ARDS may have derived from the intervention that had been proven to be beneficial in ARDS of other causes in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… [32] Moreover, the adaptation of prone ventilation in COVID-19-related ARDS may have derived from the intervention that had been proven to be beneficial in ARDS of other causes in previous studies. [29] The seminal PROSEVA trial, which showed significant reduction in mortality with prone positioning being applied early in the course of disease (< 24 hours) for prolonged periods (> 16 hours per session), was likely a fundamental contributing factor. [ 33 , 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…Proning is a proven intervention to reduce mortality in ARDS 13 , 14 and is a cornerstone of therapy in COVID-19. 15 The duration of daily proning in patients with COVID-19 ARDS is similar (~16 hr) 16 to randomized controlled trials (RCTs) identified in a systematic review of moderate-to severe ARDS (16–18 hr). 17 Nevertheless, recurrent, daily proning requires sustained deep coma and prolonged paralytic use, which may promote muscle unloading and further exacerbate ICU-acquired weakness.…”
Section: Discussion and Literature Contextmentioning
confidence: 81%
“…103 Stilma et al, in a multicenter retrospective study in 734 patients from 22 centers in the Netherlands, found that prone positioning was applied in 60% of the patients and was performed for a median for 15 hours/day; patients in whom prone positioning was not performed despite a clinical indication had increased 90-day mortality. 104 Finally, Mathews et al, in large retrospective cohort study on 2,338 patients from 68 ICUs in the United States with a PaO 2 /FiO 2 <200 mm Hg, found that early proning (within 2 days from admission to ICU) was associated with a survival benefit. 105 The use of very prolonged periods of prone positioning (up to 48 consecutive hours) has been described as feasible and safe in patients with COVID-19 ARDS, and may help to reduce the workload of health care workers during pandemic waves without increasing risks.…”
Section: Rescue Treatments Prone Position-from Rescue To Routinementioning
confidence: 99%